Crash course in library supervision meeting the key players - Tucker, Dennis C. (Crash course series (Westport, Conn.), 2008)
Managing a small library requires skills in working with personnel, the library board, patrons, and the key people in the community. Understanding these requirements will help the person with no formal education to be a more effective administrator in this setting.